Effect of cultivation mode on the production of docosahexaenoic acid by Tisochrysis lutea - Hao Hu; Lin-Lin Ma; Xiao-Fei Shen; Jia-Yun Li; Hou-Feng Wang; Raymond Jianxiong Zeng (AMB Express, 2018)
Abstract In this study, Tisochrysis lutea was cultivated in mixotrophic and heterotrophic cultures with glycerol as a carbon source and with glucose and acetate for comparison; autotrophic cultivation was the control group without a carbon source. It was found that T. lutea used glycerol and did not use glucose and acetate under mixotrophy. Mixotrophy slightly elevated the docosahexaenoic acid (DHA) and total fatty acids (TFA) content in the dry-weight and enhanced the DHA and TFA production in medium (41.3 and 31.9% respectively) at the end of a 16-day cultivation, while heterotrophy reduced the DHA content and TFA production. Under the mixotrophy, the glycerol contribution to the DHA production (16.19 mg/L) and the TFA production (97.8 mg/L) was not very high and the DHA yield [2.63% chemical oxygen demand (COD)] and TFA yield (13.1% COD) were also very low. Furthermore, T. lutea using glycerol had a period of adaptation, indicating that T. lutea was not an ideal microalga for organic carbon utilization.